PENGETAHUAN, SIKAP DAN KELENGKAPAN PENGGUNAAN ALAT PELINDUNG DIRI DI UNIT PERAWATAN INTENSIF RUMAH SAKIT - Sholeh, Wahidin; Yogisutanti, Gurdani; Fuadah, Fahmi (Jurnal Ilmu Kesehatan Immanuel, 2023)
The use of PPE must be in accordance with standard operating procedures (SOP), to prevent work accidents and hazards that may arise when working in a hospital. The research objective was to determine the relationship between knowledge, attitudes and use of PPE at HA Rotinsulu Pulmonary Hospital, Bandung. The type of survey used is descriptive-quantitative with a cross-sectional design. The sample for the study was 42 nurses working in surgical facilities and the Intensive Care Unit (ICU). Most of the respondents had good knowledge (71.0%) and a positive attitude (61.0%) and some of the compliance with the use of PPE was still incomplete in using PPE (57.0%). Based on Spearman's correlation analysis, a p-value of 0.146 was obtained for the relationship between knowledge and use of PPE, and 0.069 for the relationship between attitude and use of PPE. The results showed that there was no relationship between knowledge and attitudes with the use of PPE in ICU care. Compliance with the use of PPE in hospitals is not related to the level of knowledge or attitudes of nurses. The need to establish SOPs on the use of PPE in hospitals to increase the compliance of nurses who have not used PPE. Keywords: PPE, Knowledge, Attitude, and Compliance.